Proceedings of the 1st International Conference on Social-Humanities in Maritime and Border Area, SHIMBA 2022, 18-20 September 2022
DOI: 10.4108/eai.18-9-2022.2326017
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Electoral Law to Increase The Participation of Coastal Communities in Simultaneous Elections in Indonesia: A Study on Coastal Communities of Kepulauan Riau Province

Abstract: Every eligible citizen has the right to vote, even if their economic, social, or geographical situation makes it hard for them to do so, as is the case for coastal communities. However, the participation of coastal communities in elections are political right and must be realized by the state, as mandated by the law. This study aims to see what the participation of coastal communities in Bintan and Kota Tanjungpinang Regencies is like and how the concept of reconstruction of the electoral law in increasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Conclusión: La presencia de la ley es necesaria para ayudar al proceso de cambio de la sociedad hacia la renovación. Se necesitan tres cosas para cumplir con el derecho de voto pasivo de las Haryanti, D., Setyawanta, L., T., Adhayanto, O., Rani, M., & Irman. (2024).…”
Section: Cumplimiento Del Derecho De Voto Pasivo De Las Comunidades C...unclassified
See 3 more Smart Citations
“…Conclusión: La presencia de la ley es necesaria para ayudar al proceso de cambio de la sociedad hacia la renovación. Se necesitan tres cosas para cumplir con el derecho de voto pasivo de las Haryanti, D., Setyawanta, L., T., Adhayanto, O., Rani, M., & Irman. (2024).…”
Section: Cumplimiento Del Derecho De Voto Pasivo De Las Comunidades C...unclassified
“…In general, the participation of coastal communities in fulfilling voting rights is still limited to active voting rights and only to certain stages such as the voting stage in each election activity as from the results of previous research in Riau Islands Province which concluded that the voter participation rate in the 2019 legislative election had reached the national target of 77.5% but only limited to participation in the voting stage because they were more Focus on making a living. (Haryanti et al, 2022) Meanwhile, the fulfilment of passive voting rights has not been a concern because of their lack of confidence to compete as candidates for legislative members.…”
Section: Passive Suffrage Of Coastal Communitiesmentioning
confidence: 99%
See 2 more Smart Citations